Neoepitopes at the crossroads of immunometabolism: metabolic remodeling of antigen presentation in type 1 diabetes - Mittal, Rahul; Goldmann, Rebecca; Mittal, Mannat; Chaudhary, Naisha; Ravindra, Vibha; Hirani, Khemraj (Frontiers in Immunology, 2026)
Type 1 diabetes (T1D) is an autoimmune disorder driven by progressive destruction of pancreatic β-cells under conditions of metabolic and oxidative stress. This article examines the intersection of immunometabolism and antigen presentation as a central mechanism in T1D pathogenesis. In β-cells, endoplasmic reticulum (ER) stress, mitochondrial dysfunction, and redox imbalance remodel the immunopeptidome, promoting neoepitope formation and upregulation of major histocompatibility complex class I (MHC-I) molecules. Concurrently, antigen-presenting cells (APCs) exposed to hypoxia, cytokines, and nutrient deprivation undergo metabolic reprogramming that enhances glycolysis, reactive oxygen species (ROS) production, and pro-inflammatory antigen processing. These parallel responses establish a self-sustaining β-cell–APC loop in which metabolic distress in one cell type amplifies dysfunction in the other. By integrating evidence from redox signaling, immunopeptidomics, and metabolic regulation, this perspective defines a unified framework wherein metabolism acts as both initiator and amplifier of autoimmunity. Targeting the immunometabolic interface between β-cells and APCs may restore immune tolerance and prevent disease progression by re-establishing cellular homeostasis.